2020
DOI: 10.19044/esj.2020.v16n21p364
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Variation of Seedling Growth and Leaves Type of Four Morphotypes of Lannea Microcarpa Engl.& K. Krause in Burkina Faso

Abstract: This study evaluated the growth performance and the leaves type of seedlings from different morphotypes of Lannea microcarpa in the central plateau of Burkina Faso.Then, seeds of Lannea microcarpa were collected from four (4) morphotypes based on their botanical characters and noted as NLs: Lannea sp. from Naab-Mayooghin, MLs: from Mamousyorgo 1, MaLs: from Mamousyorgo2, ZLs: from Ziniaré. One hundred seeds per morphotypes were used for the seedlings production in nursery through sowing by using a randomized b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
0
0
Order By: Relevance
“…This highlighted that these individuals are of the same kind. These results confirmed those obtained from the morphological characterization previously carried out by [5]. The sequencing of the various genes allowed the grouping of the individuals into several subgroups.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This highlighted that these individuals are of the same kind. These results confirmed those obtained from the morphological characterization previously carried out by [5]. The sequencing of the various genes allowed the grouping of the individuals into several subgroups.…”
Section: Discussionsupporting
confidence: 87%
“…According to surveys of residents, these trees are between 80 and 90 years old. However, these individuals exist in small numbers (4 trees) and do not seem to have been encountered elsewhere [5]. Studies have shown that these individuals come from the same ecological environment as Lannea microcarpa [6].…”
Section: Introductionmentioning
confidence: 99%